Non-coding RNAs as Regulators of Lymphangiogenesis in Lymphatic Development, Inflammation, and Cancer Metastasis - Cao, Ming-xin; Tang, Ya-ling; Zhang, Wei-long; Tang, Ya-Jie; Liang, Xin-hua (Frontiers in Oncology, 2019)
Noncoding RNAs (ncRNAs), which do not encode proteins, have pivotal roles in manipulating gene expression in development, physiology, and pathology. Emerging data have shown that ncRNAs can regulate lymphangiogenesis, which refers to lymphatics deriving from preexisting vessels, becomes established during embryogenesis, and has a close relationship with pathological conditions such as lymphatic developmental diseases, inflammation and cancer. This review summarizes the molecular mechanisms of lymphangiogenesis in lymphatic development, inflammation and cancer metastasis, discusses ncRNAs’ regulatory effects on them. And therapeutic targets with regard to lymphangiogenesis are also involved.